Undocumented secrets of MATLAB-Java programming - Altman, Yair M. (CRC Press, 2012)
"Preface The Matlab programming environment uses Java for numerous tasks, including networking, data-processing algorithms, and graphical user-interface (GUI). Matlab's internal Java classes can often be easily accessed and used by Matlab users. Matlab also enables easy access to external Java functionality, either third-party or user-created. Using Java, we can extensively customize the Matlab environment and application GUI, enabling the creation of very esthetically pleasing applications. Unlike Matlab's interface with other programming languages, the internal Java classes and the Matlab-Java interface were never fully documented by The MathWorks (TMW), the company that manufactures the Matlab product. This is really quite unfortunate: Java is one of the most widely used programming languages, having many times as many programmers as Matlab. Using this huge pool of knowledge and components can significantly improve Matlab applications. As a consultant, I often hear clients claim that Matlab is a fine programming platform for prototyping, but is not suitable for real-world modern-looking applications. This book aimed at correcting this misconception. It shows how using Java can significantly improve Matlab program appearance and functionality and that this can be done easily and even without any prior Java knowledge. In fact, many basic programming requirements cannot be achieved (or are difficult) in pure Matlab, but are very easy in Java. As a simple example, maximizing and minimizing windows is not possible in pure Matlab, but is a trivial one-liner using the underlying Java code"-- Provided by publisher